The ambivalence of social change: Triumph or trauma? - Piotr Sztompka (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2000)
Sociological approaches to social change have evolved in three typical forms: the discourse of progress in the period of classical sociology, the discourse of crisis characteristic for the middle of the XXth century, and the discourse of trauma, which seems to emerge at the end of the XXth century. The concept of trauma, borrowed from medicine, suggests that change per se, irrespective of its content, but provided that it is sudden, comprehensive, fundamental and unexpected, may produce painful shock for the social and particularly cultural tissue of a society. Paradoxically, this applies also to changes which are otherwise progressive, welcome, and intended by the people. Cultural trauma begins with disorganization of cultural rules and accompanying personal disorientation, culminating even in the loss of identity. This condition is made more grave by the traumatizing events or situations which occur as the effect of major change in areas other than culture, and affect the whole lifeworld of the people. The traumatic mood which spreads in a society is countered by various coping strategies. If they are successful trauma turns out into mobilizing force for human agency, and stimulates creative social becoming. Such theoretical model is applied and tested with data referring to the radical political, economic and cultural transformations in the countries of Central and Eastern Europe after the collapse of communism. The analysis of the Polish case suggests that the model of trauma and slow re-consolidation of culture may be an adequate interpretative tool for this unique historical process.
Keywords: 300